Foreign tourism in San Jose downtown: volume, areas and resources used and impact on the environment - Mora, Eduardo (2013)
It presents the results of a study, conducted in 2011 and the first half of 2012, on some of the most important aspects of tourism in San Jose center: defining characteristics of tourists in this geographical space, activities carried out, areas and establishments that used and characteristics of these, major changes in land use in tourist areas and transformations -or inertia- in the landscape, hygiene, roads and transportation, safety and quality of public spaces. The collection of information was made ​​in the field: GPS and “manual” inventories, scheduled observation, surveys and interviews. Mainly, it was concluded that since the late eighties, when tourist hatching occurred in Costa Rica, in small areas of San José downtown the establishments of interest and tourist use proliferated, but all of small dimensions (the relatively large are precedents). Consequently, the impact of tourism on the urban is not significant and is imperceptible in many ways, showing relevant only in a small area. In addition, tourism in San Jose downtown tends to decrease.